2020
DOI: 10.1098/rsbl.2020.0033
|View full text |Cite
|
Sign up to set email alerts
|

A review of research in primate sanctuaries

Abstract: While non-human primate studies have long been conducted in laboratories, and more recently at zoological parks, sanctuaries are increasingly considered a viable setting for research. Accredited sanctuaries in non-range countries house thousands of primates formerly used as subjects of medical research, trained performers or personal pets. In range countries, however, sanctuaries typically house orphaned primates confiscated from illegal poaching and the bushmeat and pet trafficking trades. Although the primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 284 publications
(285 reference statements)
1
19
0
Order By: Relevance
“…This creates opportunities for research to be conducted at certain facilities or with certain individuals and species in which invasive procedures are not permitted or feasible. For example, while zoos and sanctuaries house a higher diversity of species than do traditional research settings, they typically are not able to accommodate research protocols that require extensive training, separation of primates from group mates, or invasive protocols (Hopper, 2017;Ross & Leinwand, 2020). Noninvasive and restraint-free approaches offer the potential for eye-tracking research to be conducted in such settings, meaning a greater variety of individuals and species could be tested, expanding our understanding of cognition across and within species.…”
Section: Noninvasive and Restraint-free Eye-tracking Approachesmentioning
confidence: 99%
“…This creates opportunities for research to be conducted at certain facilities or with certain individuals and species in which invasive procedures are not permitted or feasible. For example, while zoos and sanctuaries house a higher diversity of species than do traditional research settings, they typically are not able to accommodate research protocols that require extensive training, separation of primates from group mates, or invasive protocols (Hopper, 2017;Ross & Leinwand, 2020). Noninvasive and restraint-free approaches offer the potential for eye-tracking research to be conducted in such settings, meaning a greater variety of individuals and species could be tested, expanding our understanding of cognition across and within species.…”
Section: Noninvasive and Restraint-free Eye-tracking Approachesmentioning
confidence: 99%
“…Several studies have shown how study subjects that do not undergo death during invasive experiments do suffer long-term psychological effects as a consequence of their traumatic experiences in laboratories [98]. These studies have been mostly conducted on NHPs that have been moved to sanctuaries after spending several years as laboratory subjects and are therefore mostly limited to research on chimpanzees [99]. Traumatic experiences due to invasive research, for instance, are linked to the occurrence of abnormal behaviours similar to posttraumatic stress disorder and depression [100,101].…”
Section: Welfare Considerationsmentioning
confidence: 99%
“…Crockford et al, 2012;Gruber et al, 2009, for field experiments with chimpanzees). During the last two decades, an increasing number of cognitive experiments have been conducted with captive sanctuary populations of great apes, thus broadening the view of primate cognition to wild-born individuals (see Ross & Leinwand, 2020 for an overview). An important future direction in primate cognition research is to continue to find suitable experimental methods to compare primates in diverse living conditions, including the wild.…”
Section: Future Directionsmentioning
confidence: 99%